Online Teaching-Learning Practices of Science, Technology, and Society: Philippine Higher Education Context - Rivera, Kimberly Cabrera (Journal of Educational Science and Technology (EST), 2024)
The basic education system in the Philippines has transitioned from K-10 to K-12, introducing new courses in universities, including Science, Technology, and Society (STS). This course is valuable as it links science to technology and industry, vital for national growth. With STS now part of the curriculum, periodic assessments are essential to evaluate how instructors and learners are adapting, especially after the pandemic shifted classes to online and blended modalities. This narrative analysis research study was conducted to examine the online teaching and learning practices of students and teachers. The study suggests that students prefer collaborative and creative activities, asynchronous learning, practical content, and modules with visual aids rather than dense text. Teachers support students' education by using recorded videos for discussions, integrating creative assessments into various tasks, and maintaining communication through mobile instant messaging (MIM). To improve the online teaching and learning of STS, several factors are necessary. Modules should be clear and visually engaging, and content must be accurate and up-to-date. It is also important to revisit STS as a general education course to evaluate its relevance and impact, and to adapt content to local contexts. Assessments should prioritize quality over quantity, and asynchronous classes should be supported with face-to-face instruction to effectively blend online and in-person learning. Encouraging collaboration among educators to share best practices and resources is also recommended. These measures may help improve the implementation and effectiveness of STS in the Philippines' educational system to meet the present needs of both students and teachers.